Le connecteur or et ses traductions serbes - Vasiljević, Anđela (Verbum – Analecta Neolatina, 2022)
This paper deals with the contrastive analysis of the French connective or and its Serbian equivalents. Bearing in mind the complex nature that characterizes this function word and also the fact that it does not have a specific semantic correspondent in Serbian, we first offer a theoretical introduction to its main diachronic and synchronic features in an effort to identify some of the factors that conditioned its grammaticalization in French. We further focus on describing different values of its translation possibilities into Serbian. The theoretical part of the work is followed by a quantitative and qualitative analysis of aligned and contextualized examples, in order to provide a greater variety of possible pragmatic equivalents, while also paying special attention to their distribution properties. Finally, in the concluding section, we point out the most common problems related to the acquisition of this connective by Serbian-speaking learners.